Innovation and the economy. - Michie, J; Pianta, M; Oughton, C (Routledge, 2002)
Unemployment has remained at relatively high levels across most European countries for a generation now. There have been a number of suggested explanations for this, with correspondingly different policy implications. Two of the major hypotheses relate, first, to the impact on the European economies from increased international competition, and 'globalisation' more generally, and, secondly, to the effects of new technology and innovation. The effects of both globalisation and technology on growth and employment in Europe have been researched over the past two years through an EU-funded project, the results of which, relating in particular to innovation, are reported in this Special Issue of the International Review of Applied Economics . (The results relating to globalisation were reported in a Special Issue of the Journal of Interdisciplinary Economics , Volume 13.) It is clear from the empirical work reported that the effects of technological innovation have been mixed. There is no doubt that some innovation has had a negative effect on employment, without the compensatingly positive effects that new technology usually brings in its wake. However, in high technology manufacturing sectors there is scope for boosting both productivity and employment. But this requires an appropriate policy environment, conducive to increased investment in capital, R&D; and the workforce itself.